2019
DOI: 10.1038/s41598-019-54027-y
|View full text |Cite
|
Sign up to set email alerts
|

A SUMO-dependent pathway controls elongating RNA Polymerase II upon UV-induced damage

Abstract: RnA polymerase ii (RnApii) is the workhorse of eukaryotic transcription and produces messenger RnAs and small nuclear RnAs. Stalling of RnApii caused by transcription obstacles such as DnA damage threatens functional gene expression and is linked to transcription-coupled DnA repair. to restore transcription, persistently stalled RnApii can be disassembled and removed from chromatin. this process involves several ubiquitin ligases that have been implicated in RnApii ubiquitylation and proteasomal degradation. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Its degradation might be a consequence of transcription stalling due to roadblocks ahead of RNA polymerase II. In fact, under these circumstances Rpb1 degradation was described to rely on the ubiquitin-proteasome system, the ATPase Cdc48/p97 and SUMO 91 , 92 . At any rate, a stalled, non-crosslinked Rpb1 would be equally “eligible” for degradation by DPC proteases, since other “non-DPC” substrates exist and will be discussed later in this review.…”
Section: Dpc Proteasesmentioning
confidence: 99%
“…Its degradation might be a consequence of transcription stalling due to roadblocks ahead of RNA polymerase II. In fact, under these circumstances Rpb1 degradation was described to rely on the ubiquitin-proteasome system, the ATPase Cdc48/p97 and SUMO 91 , 92 . At any rate, a stalled, non-crosslinked Rpb1 would be equally “eligible” for degradation by DPC proteases, since other “non-DPC” substrates exist and will be discussed later in this review.…”
Section: Dpc Proteasesmentioning
confidence: 99%
“…Although these data strongly link RNAPIII sumoylation with a positive effect on its transcriptional activity, using genetic analysis, another study found that impairing sumoylation could at least partly rescue the growth defects associated with mutant forms of RNAPIII subunits, suggesting that in some conditions, sumoylation can repress RNAPIII activity [25]. Also in yeast, the elongation-associated form of RNAPII was found to become sumoylated on its large subunit, Rpb1, in response to UV irradiation or impairment of transcription, implicating the modification in the resolution of transcriptionally stalled RNAPII complexes at DNA lesions [26,27]. In human cells, both TBP and multiple TAF subunits of TFIID are known SUMO targets, and in in vitro assays, sumoylation of hsTAF5 was found to inhibit binding of this GTF to an immobilized DNA template, suggesting that TFIID sumoylation might be involved in regulating the assembly of the complex with promoters [6,9,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Prominent among those is CTCF, a canonical TAD insulator, whose known accumulation at DSB-flanking chromatin microdomains ( 68 , 69 ) is consistent with transcriptional deregulation described in our study. Firstly, CTCF anchor engagement per se seems enhanced under conditions of RNAPII removal ( 70 ), such as the one that can occur at damaged chromatin ( 7173 ). Additionally, several non-coding RNAs have been implicated with CTCF eviction to regulate local chromatin folding ( 7476 ), consistent with the possibility that reduced retention of RNA species at post-repair chromatin as shown in our study could foster ectopic CTCF accumulation.…”
Section: Discussionmentioning
confidence: 99%